Analisis Keamanan Jaringan Pada Pay2home Menggunakan Metode Penetration Testing - Stefanus Eko Prasetyo; Ricky Chandra Lee (Universitas Internasional Batam, 2021)
Penetration Testing is a method used in finding loopholes in the system, in order to minimize attacks and breaches in a company website network. In tests carried out on the pay2home network at shremit.p2hdevworks.com using several penetration testing applications to test network security including Nessus, Acunetix, W3af, and Nmap. Where each of these applications functions to test attacks and look for security gaps on the network and system, the variables that are the reference in this trial are the gaps that are obtained, where the results of the research show that the pay2home.com network website has a fairly high security.